Suicide Attempts in an Adolescent Female Twin Sample - GLOWINSKI, ANNE L. (2001)
OBJECTIVE: To examine suicide attempts in an epidemiologically and genetically informative youth sample. METHOD: 3,416 Missouri female adolescent twins (85% participation rate) were interviewed from 1995 to 2000 with a telephone version of the Child Semi-Structured Assessment for the Genetics of Alcoholism, which includes a detailed suicidal behavior section. Mean age was 15.5 years at assessment. RESULTS: At least one suicide attempt was reported by 4.2% of the subjects. First suicide attempts were all made before age 18 (and at a mean age of 13.6). Major depressive disorder, alcohol dependence, childhood physical abuse, social phobia, conduct disorder, and African-American ethnicity were the factors most associated with a suicide attempt history. Suicide attempt liability was familial, with genetic and shared environmental influences together accounting for 35% to 75% of the variance in risk. The twin/cotwin suicide attempt odds ratio was 5.6 (95% confidence interval [CI] 1.75–17.8) for monozygotic twins and 4.0 (95% CI 1.1–14.7) for dizygotic twins after controlling for other psychiatric risk factors. CONCLUSIONS: In women, the predisposition to attempt suicide seems usually to manifest itself first during adolescence. The data show that youth suicide attempts are familial and possibly influenced by genetic factors, even when controlling for other psychopathology.